Acute traumatic abdominal wall hernia—value of the physical examination: case report - Hernandez Cervantes, Barbara Yordanis (J Surg Case Rep, 2021)
Acute traumatic abdominal wall hernia (TAWH) is a rare type of hernia that occurs after a low or high velocity impact of the abdominal wall against a blunt object with few cases reported. Perforations of the hollow viscera commonly follow abdominal trauma and likely require surgery for hemorrhage and sepsis source control. We report a case where a high velocity impact of the abdominal wall against the stump of a felled tree caused a TAWH with concomitant gastric perforation in a 20-year-old male patient who required exploratory laparotomy with primary repair of the stomach and fascia. The physical examination findings without previous history of abdominal hernia and pneumoperitoneum in the chest X-ray made suspect our diagnosis and it was confirmed intraoperatively. At 3 months postoperatively the patient has a strong abdominal wall. It is imperative to emphasize the importance of the physical examination goal of not losing diagnosis of TAWH.